FRI0182 A Single Dose Study Comparing Pharmacokinetics, Safety, and Immunogenicity of M923 (A Proposed Biosimilar To Adalimumab), US-Sourced Adalimumab, and EU-Sourced Adalimumab in Healthy Subjects. (15th July 2016) - Hillson, J.; Mant, T.; Ganguly, T.; Rosano, M.; Huntenburg, C.; Alai-Safar, M.; Darne, S.; Palmer, D.; Pavlova, B.; Doralt, J.; Reeve, R.; Goel, N.; et al.
Abstract : Background: M923 is being developed as a biosimilar to the reference product HUMIRA® (adalimumab). An extensive panel of tests were used to characterize the physicochemical, functional, and in vivo attributes to support the initiation of clinical testing. Objectives: The primary objective of this study was to evaluate pharmacokinetic (PK) equivalence between M923 and US-sourced adalimumab, between M923 and EU-sourced adalimumab, and between US- and EU-sourced adalimumab. Safety and immunogenicity were also assessed. Methods: This was a randomized, double-blind, 3-arm, parallel group, single-dose study. A total of 324 healthy volunteers were randomized 1:1:1 to receive a single 40 mg dose of M923, US-sourced adalimumab, or EU-sourced adalimumab by subcutaneous injection on Day 1. Subjects were then followed for a total of 71 days; serum concentration of adalimumab, anti-drug antibodies (ADAs), and adverse events (AEs) were recorded. The primary PK endpoints were: Cmax, AUC0-inf, and AUC0–336 . PK bioequivalence was achieved if 90% confidence intervals for the geometric least squares (LS) mean ratios for all comparisons were within the confidence bounds (CI) of 80.00 to 125.00%. Results: Bioequivalence was observed for all primary PK endpoints. Specifically, for the comparison of M923 with US-sourced adalimumab, the geometric LS mean ratios (90% CI) were Cmax =102.58 (97.31–108.14); AUC0-inf =104.20 (96.47–112.54); and AUC0–336 =102.94 (97.88–108.27). Similarly, for the comparison of M923 with EU-sourced adalimumab, the geometric LS mean ratios (90% CI) were Cmax =99.39 (94.25–104.81); AUC0-inf =100.90 (93.48–108.90); and AUC0–336 =100.51 (95.55–105.73). Lastly, for the comparison of US-sourced with EU-sourced adalimumab, the geometric LS mean ratio (90% CI) were Cmax =103.21 (97.85–108.86); AUC0-inf =103.27 (95.50–111.67); and AUC0–336 =102.42 (97.30–105.81). Similar concentration-time profiles were observed across groups (graph). The incidence, type, and severity of AEs were comparable across groups. The incidence, titer, and time to emergence of ADAs at any time during the study were similar across groups (proportion of subjects with confirmed positive titers: M923 =78.0%; US-sourced adalimumab =80.6%; EU-sourced adalimumab =78.5%). Conclusions: Bioequivalence was observed for all treatment comparisons (M923/US-sourced adalimumab; M923/EU-sourced adalimumab; EU-sourced adalimumab/US-sourced adalimumab). In addition, the safety and tolerability profile of M923 was demonstrated to be comparable to what has been established in previous studies of EU-sourced adalimumab and US-sourced adalimumab. Disclosure of Interest: J. Hillson Shareholder of: Momenta, Employee of: Momenta, T. Mant Consultant for: Momenta/Baxalta, T. Ganguly Shareholder of: Momenta, Employee of: Momenta, M. Rosano Shareholder of: Momenta, Employee of: Momenta, C. Huntenburg Shareholder of: Momenta, Employee of: Momenta, M. Alai-Safar Shareholder of: Baxalta, Employee of: Baxalta, S. Darne Shareholder of: Baxalta, Employee of: Baxalta, D. Palmer Shareholder of: Baxalta, Employee of: Baxalta, B. Pavlova Shareholder of: Baxalta, Employee of: Baxalta, J. Doralt Shareholder of: Baxalta, Employee of: Baxalta, R. Reeve Consultant for: Momenta/Baxalta, N. Goel Consultant for: Momenta/Baxalta, D. Weilert Consultant for: Momenta/Baxalta, P. Rhyne Consultant for: Momenta/Baxalta, J. Caminis Shareholder of: Baxalta, Employee of: Baxalta, J. Roach Shareholder of: Momenta, Employee of: Momenta